Highly Pathogenic Avian Influenza Contributes to the Population Decline of the Peregrine Falcon (Falco peregrinus) in The Netherlands - Valentina Caliendo; Beatriz Bellido Martin; Ron A. M. Fouchier; Hans Verdaat; Marc Engelsma; Nancy Beerens; Roy Slaterus (Viruses)
Highly pathogenic avian influenza (HPAI) epizootics have caused repeated mass mortality events among wild birds. The effect of the infection is potentially detrimental for a variety of bird species, including the Peregrine Falcon (Falco peregrinus). The numbers of wintering and breeding Peregrine Falcons in the Netherlands have recently declined. We investigated the changes in population trends in relation to HPAI H5 virus outbreaks. For this purpose, we analyzed variations in annual numbers of wintering and breeding birds, the virology of reported dead birds, and the presence of the HPAI H5 virus in unhatched eggs. We showed that significant mortalities of Peregrine Falcons had occurred in 2016–2017 and 2020–2023, years of major HPAI H5 virus outbreaks. In particular, the highest rates of bird mortality and HPAI virus infection were reported in 2023. In this year, over 80% (28/32) of the tested birds were positive for HPAI H5 virus. No HPAI H5 virus was present in the eggs. Based on these findings, we concluded that HPAI represents a serious threat to the Peregrine Falcon population in the Netherlands, and, in combination with anthropogenic factors, may contribute to the decline of this species. Targeted HPAI surveillance and disease mitigation measures are necessary for the conservation of this species.